PORTRAIT OF SHARIA ACCOUNTING EDUCATION DURING THE COVID 19 PANDEMIC - Mohamad Anwar Thalib (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2023)
This study aims to reveal the feelings of joy, sorrow, and sin in students majoring in Islamic accounting when attending lectures online. This research uses a type of qualitative method with a descriptive approach. There are three data analysis stages: reduction, data presentation, and drawing conclusions. The results showed that accounting lectures held online due to the covid 19 pandemic brought a sense of happiness because students majoring in sharia accounting could gain new experience and knowledge about how to take lectures using the application, then students also felt happy because lecture time was more flexible. Lectures Online can save more on transportation costs. The grief felt by students when attending online lectures is the lack of adequate facilities such as student mobile phones, which sometimes get damaged due to prolonged use of the internet, unstable internet network, and expensive and limited internet quota. Online lectures provide opportunities for students not to take lectures seriously, including when the temporary lecturer explains that students choose to sleep, eat, wash clothes, or play on social media. They recognize this action as a sinful act that ultimately causes guilt and regret for classmates, lecturers, parents, and family.